Changes in Polyphenolic Content and Antioxidant Activity of Grapes cv Vranac During Ripening - Andjelkovic, M.; Radovanović, B.; Radovanović, A.; Andjelkovic, A.M. (South African Journal of Enology and Viticulture, 2016)
This study characterised and evaluated the phenolic composition and antioxidant activity of the red wine grape Vranac (Vitis vinifera L.) from the southern Serbian vineyard region during grape ripening. Polyphenol composition at different harvest dates was determined by HPLC-DAD analysis. Antioxidant activity was estimated by DPPH assay. The study demonstrates that the Vranac variety represents important sources of dietary antioxidants. The results show that (+)-catechin, (-)-epicatechin and procyanidin dimer B2 were the most prevalent in the seeds, and quercetin and malvidin glucosides in the grape skins. All grape extracts were shown to have high radical-scavenging activity. Strong correlations between radical-scavenging activity and polyphenols suggest that the phenolic composition of the Vranac variety contributes significantly to the antioxidant capacities of grape extracts. During grape ripening there were significant changes in physiological properties and phenolic content, and it is important to determine optimal harvest time, which will ensure grapes with very good quality parameters (in our study at the 30th day after véraison).